Digestible protein requirements for maintenance, growth, and efficiency of protein utilization in pacu (Piaractus mesopotamicus) juveniles: An exponential nitrogen utilization model - Mansano, Cleber F.M.; Silva, Edney P. [UNESP]; Khan, Kifayat U. [UNESP]; Macente, Beatrice I.; Nascimento, Thiago M.T. [UNESP]; Sakomura, Nilva K. [UNESP]; Fernandes, João B.K. [UNESP]; Takahashi, Leonardo S. [UNESP] (Pontificia Universidad Catolica de Valparaiso, 2021)
The present study aimed to estimate digestible protein (DP) requirements for maintenance and growth and assess the efficiency of protein utilization in pacu (Piaractus mesopotamicus) juveniles. A complete randomized design consisted of seven treatments, and five replicates (tanks) per treatment was used. After a one-week acclimation period, 350 pacu juveniles of 27.48 ± 1.8 g (initial average body weight-BW) were equally distributed among 35 tanks (10 fish per tank) of 450 L. Fish were fed with seven graded digestible protein levels (64.5, 111.8, 164.6, 217.1, 264.4, 316.2 and 369.5 g kg-1) three times a day until apparent satiation for 120 days. The monomolecular model parameters including nitrogen maintenance requirement (NMR) (37.76 mg BW0.67 kg-1 d-1), daily nitrogen deposition (ND) (194.8 mg BW0.67 kg-1 d-1), and protein intakes (based on metabolic BW) of 1638, 1902, and 2241 mg kg-1BW0.67 d-1 for 75, 80 and 85% maximum theoretical nitrogen retention (NRmaxT), respectively and the efficiency of protein utilization (529×10-6) were estimated through the relationship between nitrogen intake (NI) and ND. The digestible protein requirements for 75, 80, and 85% of NRmaxTwere estimated as 187, 217, and 256 g kg-1 respectively by the monomolecular model based on the daily feed intake of 2% of live BW of pacu juveniles.
Keywords: Feed intake; Maintenance requirement; Monomolecular model; Nitrogen deposition; Pacu nutrition; Piaractus mesopotamicus